Associations between critical consciousness and well‐being in a national sample of college students during the COVID‐19 pandemic. Issue 2 (5th August 2021) - Maker Castro, Elena; Dull, Brandon; Hoyt, Lindsay T.; Cohen, Alison K.
Abstract: Critical consciousness (CC) may promote well‐being, particularly during the COVID‐19 pandemic. In a national survey of 707 college students conducted in April 2020, we first validated the Short Critical Consciousness Scale (ShoCCS) among youth groups not often specifically examined in CC measurement (i.e., Asian, immigrant‐origin, LGBQ+, and women youth). Next, we examined associations between ShoCCS subscales and validated measures of both anxiety (Generalized Anxiety Disorder‐7) and hopefulness (The Individual‐Differences Measure in Hopefulness). The ShoCCS achieved measurement invariance across racial/ethnic groups and immigrant‐origin status, and partial invariance among LGBQ+ and women‐identifying youth. We found critical reflection and action associated with anxiety for the full sample, but no evidence of moderation by sociodemographic factors. ShoCCS subscales were differentially associated with hopefulness for Asian youth and LGBQ+ youth. This study contributes to the evolution of CC measurement and extends the field by identifying well‐being associations during the onset of the COVID‐19 pandemic.